(untitled) (Eurasian Journal of Learning and Academic Teaching, 2026)
This study explores the role of interactive teaching methods integrated within the STEAM (Science, Technology, Engineering, Arts, and Mathematics) framework in enhancing students’ creative thinking and learning motivation. The research is based on a conceptual-theoretical analysis supported by contemporary pedagogical literature. The study examines how interdisciplinary learning and active engagement strategies contribute to cognitive and affective development. The findings suggest that STEAMbased interactive learning environments foster originality, flexibility, and problemsolving skills while simultaneously increasing students’ intrinsic motivation and engagement. The proposed model highlights the importance of combining interdisciplinary content with interactive pedagogical approaches to achieve effective learning outcomes. The study provides theoretical insights and practical recommendations for educators seeking to improve the quality of modern education.